Antioxidant activity of high purity blueberry anthocyanins and the effects on human intestinal microbiota. (January 2020) - Zhou, Li; Xie, Minhao; Yang, Fu; Liu, Jikai
Abstract: The investigation of the composition, antioxidant activity of blueberry anthocyanins (BA) and the effects on human intestinal microbiota were carried out. The separation of anthocyanins from blueberry ( Vaccinum sp.) was performed by liquid chromatography-diode array detector-electrospray ionization-tandem mass spectrometry (LC-DAD-ESI-MS 2 ). 14 anthocyanins were tentatively identified and their concentration was determined. Among them, malvidin-3- O -glucoside was the main anthocyanin species, followed by malvidin-3- O -galactoside and petunidin-3- O -glucoside, they accounted for 44.81% of the total anthocyanins in blueberry extract. The antioxidant activities were evaluated by DPPH, ABTS +, FRAP, reducing power and superoxide anion radical scavenging activity. The result showed that the EC50 value of BA by ABTS + assay was lower than the data obtained by DPPH assay, which was 14.99 μg/mL and 26.48 μg/mL, respectively. Furthermore, the impact of BA on human intestinal microbiota were analyzed by high throughput sequencing and bioinformatics analysis. The results demonstrated that BA have impact on the microbial diversity. They could increase the relative abundances of some certain communities including Bifidobacterium spp. Our findings suggest that blueberry and blueberry extracts consumption could exert prebiotic activity which are associated with health benefits. Highlights: Malvidin-3-O-glucoside was the main blueberry anthocyanin species. The antioxidant activities were evaluated by five assays. High throughput sequencing and bioinformatics analysis was applied. Blueberry anthocyanins increased the number of Bifidobacterium .